Marketing Strategy Management Or Islamic Education Marketing - Holilur Rahman; Ghina Shafiyyah; Rafika Nur Yuliatri (al-Afkar, Journal For Islamic Studies, 2025)
This research discusses marketing strategy management in the context of Islamic education, with a focus on efforts to increase the attraction, retention and quality of educational services in Islamic educational institutions. Marketing strategic management is a systematic approach that involves planning, implementing, and evaluating various marketing activities to achieve organizational goals. In Islamic education, implementing effective marketing strategies not only helps increase the number of registrants and maintain student loyalty, but also strengthens the image of educational institutions in the eyes of the public. Islamic education marketing management is the process of planning, organizing, directing and supervising the utilization of resources which is carried out efficiently and effectively to offer Islamic education services.This study identifies several key components in an Islamic education marketing strategy, including market analysis, determining unique value (unique selling proposition), developing relevant educational programs, using digital media, and transparent communication with various stakeholders. In addition, this research highlights the importance of business ethics in marketing, in accordance with the principles of honesty and justice in Islam.The research results show that implementing an integrated and sustainable marketing strategy can increase the visibility and reputation of Islamic educational institutions. The use of social media and digital technology as marketing tools has proven effective in reaching a wider audience and facilitating better interactions with prospective students and parents. Apart from that, maintaining good relationships with the community and alumni plays an important role in supporting marketing success.The conclusions of this research underline that marketing strategies that are well designed, ethical, and in accordance with Islamic values not only contribute to the growth of Islamic educational institutions, but also strengthen the integrity and trust of society in these institutions.